Revisiting the Colonial Past in Morocco. - Maghraoui, Driss (History and society in the Islamic world., 2013)
Exploring the concept of 'colonial cultures, ' this book analyses how these cultures both transformed, and were transformed by, their various societies. Challenging both the colonial vulgate, and the nationalist paradigm, Revisiting the Colonial Past in Morocco, examines the lesser known specificities of particular moments, practices and institutions in Morocco, with the aim of uncovering a 'new colonial history.' By examining society on a micro-level, this book raises the profiles of the mass of Moroccans who were highly influential in the colonial period yet have been exclude.